2022
DOI: 10.3390/metabo12111125
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum Metabolites for Predicting Chronic Kidney Disease Progression according to Chronic Kidney Disease Cause

Abstract: Early detection and proper management of chronic kidney disease (CKD) can delay progression to end-stage kidney disease. We applied metabolomics to discover novel biomarkers to predict the risk of deterioration in patients with different causes of CKD. We enrolled non-dialytic diabetic nephropathy (DMN, n = 124), hypertensive nephropathy (HTN, n = 118), and polycystic kidney disease (PKD, n = 124) patients from the KNOW-CKD cohort. Within each disease subgroup, subjects were categorized as progressors (P) or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…In summary, each of the reviewed metabolomic studies among ADPKD patients proposed different metabolites for predicting rapid ADPKD progression, and those are: urinary lactate/ pyruvate ratio (101), urinary alanine/citrate ratio (102), urinary myoinositol/citrate ratio (103), urinary methyladenosine, ornithine and kynurenate levels (104,105) and a prognostic model incorporating hexadecenoylcarnitine, pimelylcarnitine, creatinine, acyl-alkyl-phosphatidylcholin and five different diacylphosphatidylcholines (106). Since metabolic profiling seems to be a promising strategy for predicting disease progression in ADPKD patients by reflecting the underlying dysregulated metabolism with increased glycolytic flux, all of the suggested metabolites should be verified as ADPKD prognostic biomarkers in additional prospective clinical studies.…”
Section: Metabolomic Biomarkersmentioning
confidence: 99%
“…In summary, each of the reviewed metabolomic studies among ADPKD patients proposed different metabolites for predicting rapid ADPKD progression, and those are: urinary lactate/ pyruvate ratio (101), urinary alanine/citrate ratio (102), urinary myoinositol/citrate ratio (103), urinary methyladenosine, ornithine and kynurenate levels (104,105) and a prognostic model incorporating hexadecenoylcarnitine, pimelylcarnitine, creatinine, acyl-alkyl-phosphatidylcholin and five different diacylphosphatidylcholines (106). Since metabolic profiling seems to be a promising strategy for predicting disease progression in ADPKD patients by reflecting the underlying dysregulated metabolism with increased glycolytic flux, all of the suggested metabolites should be verified as ADPKD prognostic biomarkers in additional prospective clinical studies.…”
Section: Metabolomic Biomarkersmentioning
confidence: 99%
“…Interestingly, the kidney has an important role in glomerular uptake, tubular secretion, and catabolism of the majority of metabolites. Several longitudinal studies have been applied for metabolomic profiling in CKD patients [ 9 , 10 ]. For example, a Korean study that followed up 1741 subjects for 8 years showed a positive correlation between kynurenine and kynurenine/tryptophane ratio and new-onset CKD.…”
Section: Introductionmentioning
confidence: 99%
“…The decline in insulin sensitivity is the main reason for the development of hyperglycemia. This is the basis and the main cause of the microangiopathies which lead to ocular, kidney and neural pathology, and atherosclerosis, which results in cardiovascular complications [31][32][33][34]. What is more, insulin resistance has an influence on lipids metabolism and protein synthesis.…”
Section: Introductionmentioning
confidence: 99%